Effect of vitamin or mineral supplementation on oxidation and quality traits of fresh and aged beef - Ramos, Jenifer Maira Lima (2022)
This study was divided into two experiments. The first experiment with the use of fat-soluble vitamins (ADE) and/or water-soluble vitamins (biotin, niacin and thiamine) via diet in Nellore cattle. The second experiment with the use of vitamins AE and microminerals (Se, Mn, Zn and Cu) injected in crossbred cattle (¾ Angus, ¼ Nellore). Each of the two experiments originated a chapter of this thesis, totaling two chapters. In the first chapter, the effect of supplementation with a mix of B vitamins (biotin, niacin and thiamine), mix of vitamins (ADE) or a combination of these mixes on oxidation parameters, antioxidant status and quality of beef was evaluated. Nellore. Forty Nellore bulls, with a mean age of 8 ± 1 month and mean body weight of 261 ± 27.3 kg, were randomly assigned to four treatments: (a) without vitamin supplementation (Control); (b) vitamin B (B) mix supplementation; (c) mix supplementation of fat-soluble vitamins (ADE); and (d) combination of mixes (ADE + B). At the end of the 140-day period, the longissimus lumborum muscle was collected for analysis of meat quality, antioxidant enzyme activities and lipid oxidation at 1h, 24h, 196h and 360h postmortem. Supplementation with ADE and ADE+B increased intramuscular fat content, oxymyoglobin (OMb) and decreased metmyoglobin (MMb) at 196h and 360h postmortem, and decreased deoxymyoglobin (DMb) 196h postmortem, increased the Myofibrillar Fragmentation Index (MFI) 24h, 196h and 360h postmortem. In addition, ADE supplementation increased superoxide dismutase (SOD) and Ferric Antioxidant Reducing Power (FRAP), decreased glutathione peroxidase (GPx) and nitric oxide 24h postmortem, increased catalase and FRAP 196h postmortem, and increased FRAP and decreased malondialdehyde (MDA) 360 hours postmortem. In the second chapter, the effects of injectable supplementation of vitamins A and E and micro-minerals (Se, Mn, Zn and Cu) applied at weaning (D), castration (C) and pre- slaughter (PA) or their combination on meat quality, antioxidant status and lipid oxidation of crossbred cattle (¾ Angus ¼ Nellore). One hundred and twenty crossbred cattle, with a mean age of 7 ± 1 month and mean body weight of 304.58 ± 33 kg, were randomly assigned to six treatments: (N=20): (i) 000-Control (saline solution (SS) on D , C and PA; (ii) DCA - Vitamin- mineral complex (MVC) in D, C and PA; (iii) DC0 - MVC in D and C + SS in PA; (iv) D0A - MVC in D + SS in C + CVM in the PA; (v) 00A - SS in the D and C + CVM in the PA; (vi) 0CA– SS in the D + CVM in the C and PA. At the end of the period of 250 days, the collection was performed for the analyzes of meat quality, antioxidant enzyme activities and lipid oxidation in longissimus thoracis and lumborum muscle 1h, 24h, 196h and 360h postmortem. 192h and 360h postmortem. The shear force variable showed a difference 24h and 192h postmortem. Antioxidant activity (CAT and FRAP) and MDA showed a difference 1h postmortem. SOD and FRAP 24h postmortem, FRAP and MDA 192h postmortem and CAT and FRAP 360h postmortem. In the longissimus lumborum muscle, the Hue, MMb and OMb variables were different 24 hours postmortem. The variables a*, chroma and OMb showed a difference 192 hours postmortem and the variables a*, b* and chroma showed a difference 360h postmortem. FRAP showed difference 24h and 360h postmortem, GPx and SOD 360h postmortem. The use of CVM at least in PA reduces the oxidation of OMb to MMb and provides greater antioxidant status and decreased lipid oxidation. Keywords: Antioxidants. Colour. Myoglobin. Oxidation.